The Problem of Food Security in the Indonesia Border Area of Nusa Tenggara Timur Province with Timor Leste Country - Sariguna Johnson Kennedy, Posma (KnE Social Sciences, 2023)
Areas in Nusa Tenggara Timur (NTT) have a high food vulnerability. This study aims to analyze food security in the NTT border region with Timor Leste, thus understanding how to strengthen community food security. The research method used is descriptive to provide a systematic, factual description of the facts, and characteristics of the phenomena investigated. The low performance of farming influences food vulnerability due to the nature of rainfall that does not support agriculture and the little ability of farmer governance and access to innovation and technology. Food security policy strengthens and is needed for border communities and outermost islands. The average distance from the town to the nearest permanent/semi-permanent market is too far. The local community’s strategy in dealing with a food vulnerability situation resulting from the hunger risk is to use food that has existed in the past, according to naturally occuring local wisdom. The problem of food security on the border of East Nusa Tenggara needs to be a top priority for Indonesia’s development on the border. Keywords: food security, agriculture, border area, Nusa Tenggara Timur, Timor Leste